The development of targeted new agents to improve the outcome for children with leukemia. (1st November 2016) - Bautista, Francisco; Van der Lugt, Jasper; Kearns, Pamela R.; Mussai, Francis J.; Zwaan, C. Michel; Moreno, Lucas
ABSTRACT: Introduction: Survival rates in pediatric leukemia have greatly improved in the last decades but still a substantial number of patients will relapse and die. New agents are necessary to overcome the limitations of conventional chemotherapy and hematopoietic stem cell transplantation and to reduce their undesirable long-term toxicities. The identification of driving molecular alterations of leukemogenesis in subsets of patients will allow the incorporation of new-targeted therapies. Areas covered: In this article the authors present a detailed review of the most recent advances in targeted therapies for pediatric leukemias. A comprehensive description of the biological background, adult data and early clinical trials in pediatrics is provided. Expert opinion: Clinical trials are the way to evaluate new agents in pediatric cancer. The development of new drugs in pediatric leukemia must be preceded by a solid biological rationale. Agents in development exploit all possible vulnerabilities of leukemic cells. Drugs targeting cell surface antigens, intracellular signaling pathways and cell cycle inhibitors or epigenetic regulators are most prominent. Major advances have occurred thanks to new developments in engineering leading to optimized molecules such as anti-CD19 bi-specific T-cell engagers (e.g. blinatumomab) and antibody-drug conjugates. The integration of new-targeted therapies in pediatric chemotherapy-based regimens will lead to improved outcomes.